Meeting radiation therapy patients informational needs through educational videos augmented by 3D visualisation software. Issue 1 (27th February 2017) - Williams, Katelyn; Blencowe, Jenna; Ind, Melissa; Willis, David
Abstract : The aim of this project was to determine the utility of locally produced treatment process videos in meeting patients' informational needs. The 3D visualisation software assisted in explaining the need for the planning scan, dosimetry technicalities and treatment delivery in a range of patients. Abstract: Introduction: Misconceptions and uncertainties about radiotherapy compound the anxiety patients experience at the commencement of treatment. This project investigated the utility of locally produced treatment process videos in meeting patients' informational needs. Methods: In‐house video production was conducted on a voluntary basis by staff and patients at a regional Australian radiotherapy centre. Videos included real footage and animated sections created with PEARL TM 3D visualisation software (Vertual Ltd, UK) to meet specific key content objectives. Quantitative cross sectional analysis was conducted. Patients attending for simulation watched a relevant video. After their first fraction of radiotherapy they were asked to complete an ethics‐reviewed questionnaire about how well the video addressed their information needs. Results: The survey completion rate was 29% ( n = 61/212). Surveys were collected over 9 months from August 2014 to April 2015. Statistical analysis found 98% of patients reported that the video was useful in meeting one or more of the learning objectives. Forty‐nine percent of patients also reported a reduction in fear and anxiety as a result of watching the video. Patients reported subsequent review of videos at home (39%), primarily to explain treatment processes to loved ones (46%). Conclusion: The combination of real footage and 3D visualisation software assisted in meeting learning objectives regarding the treatment process. Standardised videos provided consistency of information provision to patients and facilitated multiple viewings of the video if desired.